2012
DOI: 10.1016/j.adolescence.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Romantic relationships and adjustment problems in China: The moderating effect of classroom romantic context

Abstract: Theoretical and empirical research has shown that adolescent romantic relationships are associated with a wide range of developmental outcomes, including adverse consequences. The present study used a hierarchical linear model to examine the moderating effect of classroom romantic context on the association between adolescent romantic relationships and adjustment problems. Data were collected from 4776 Chinese adolescents across 106 classes and from 47 schools. The participants' ages ranged from 12 to 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 83 publications
(81 reference statements)
5
8
1
Order By: Relevance
“…Previous studies indicated that romantic relationship involvement was associated with lower academic performance (for girls only; Brendgen et al, 2002), greater externalizing symptoms (Hou et al, 2013), and more sexual partners (for those who had a serious relationship before age 16; Zimmer-Gembeck & Collins, 2008); however, the current study's results illustrated that these associations may be more complex further supporting the need for researchers to use person-centered analytic techniques. For example, adolescents with higher quality romantic relationships reported greater academic self-efficacy than those with both satisfactory and lower quality romantic relationships.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies indicated that romantic relationship involvement was associated with lower academic performance (for girls only; Brendgen et al, 2002), greater externalizing symptoms (Hou et al, 2013), and more sexual partners (for those who had a serious relationship before age 16; Zimmer-Gembeck & Collins, 2008); however, the current study's results illustrated that these associations may be more complex further supporting the need for researchers to use person-centered analytic techniques. For example, adolescents with higher quality romantic relationships reported greater academic self-efficacy than those with both satisfactory and lower quality romantic relationships.…”
Section: Discussioncontrasting
confidence: 69%
“…These data come from adolescents from China where the incidence of romantic relationships in adolescence is lower than the incidence in the U.S.(16% males, 12% females as opposed to 53% males and 67% females in the US) (Hou et al 2013). Nonetheless, they are consistent with data from the U.S., suggesting that adolescent romantic relationships are associated with adjustment problems.…”
Section: Classroom Contextsupporting
confidence: 77%
“…Our data revealed that a substantial proportion of current or past daters among Chinese adolescents (approximately one third), especially among Taiwanese teenagers. Such prevalence is similar to Chen et al's (2009) findings among Beijing adolescents (25% to 30%) and higher than Hou et al (2013) and Li et al's (2010) findings (10% to 20%). Such discrepancy could be attributed to regional difference given that Shanghai and Taiwan, like Beijing, are highly modernized compared to the areas that the Hou et al (2013) and Li et al (2010) studied and possibly have more liberal romantic values.…”
Section: Discussionsupporting
confidence: 89%